Allelic state of prolamin-coding loci in the new oat cultivar ‘Tobolyak’ - A. V. Lyubimova; M. N. Fomina; D. I. Eremin; V. S. Mamaeva; V. S. Mishechkina; N. A. Bragin; S. A. Belousov; M. V. Bragina (Труды по прикладной ботанике, генетике и селекции)
Background. In order to fully reveal the advantages of a cultivar and use it effectively in production, it is necessary to ensure high sowing and varietal qualities of seeds, which requires improvement in breeding and seed production. Biotechnological methods are increasingly used in initial seed production. High efficiency was shown by the method of electrophoresis of seed storage proteins – prolamins. The aim of this study was to assess the biotype composition and allelic state of the prolamin-coding loci in the new spring oat cultivar ‘Tobolyak’ for its further use in initial seed production.Materials and methods. In 2021, 1519 families of cv. ‘Tobolyak’ were studied using the method of native electrophoresis. Three grains from each family were selected for analyses by random sampling. Electrophoresis was carried out in vertical plates of 13.2% polyacrylamide gel at a constant voltage of 500 V for 4.5–5.0 hours.Results and conclusion. The study of cv. ‘Tobolyak’ families resulted in identifying 13 types of avenin patterns with a frequency of occurrence from 96.36 to 0.07%. A new block of avenin components controlled by the allele of the Avn B locus was described. Number 8 was assigned to this block. It was established that cv. ‘Tobolyak’ had been developed by crossing a minor biotype of cv. ‘Taezhnik’ (Avn 4.4.2) with the first biotype of cv. ‘Orion’ (Avn 2.8.2). The basis of cv. ‘Tobolyak’ was one genotype with the Avn 4.8.2 avenin formula. The remaining biotypes arose as a result of crossing the biotypes of cvs. ‘Taezhnik’ and ‘Orion’ as well as through mechanical contamination. To maintain the genetic stability of cv. ‘Tobolyak’, it is recommended to use only families of the first biotype in the process of original seed production.